DEVELOPMENT OF LITA (LIQUID TILT ACCELEROMETER): AN ALTERNATIVE INSTRUMENT FOR ACCELERATION MEASUREMENT IN LINEAR MOTION EXPERIMENTS - Endah Nur Syamsiah; Muhammad Rizka Taufani; Adam Hadiana Aminudin; Hilman Panji Firdaus; Adit Putra (UIN Sunan Gunung Djati Bandung, 2026)
This study aims to design an alternative instrument for measuring acceleration in linear motion dynamics experiments, named LiTA (Liquid Tilt Accelerometer). The research employed a Research and Development (R&D) method using the ADPT (Analysis, Design, Prototyping, and Testing) approach. The needs analysis stage was conducted using a questionnaire, and the data were analyzed with VOSviewer. The results of the needs analysis revealed that the required experimental instrument should be easily obtainable at an affordable cost, simple in both operation and maintenance, and Integrated technology with digital support is already available. The design of LiTA utilizes the movement of water in a vessel mounted on a dynamics cart. The object’s acceleration is determined based on the inclination of the water surface inside the vessel. The prototyping of LiTA used transparent acrylic with black striped transparent stickers attached as a reference to help measure the air slope in the vessel. The testing process was carried out by conducting experiments to measure the acceleration of an object, and the results were compared with the theoretical acceleration values. The experimental data were analyzed using a paired sample t-test and the Bland–Altman plot method. The results of the paired sample t-test showed a p-value greater than 0.05, specifically 0.079, at a 95% confidence level. This indicates that there is no significant difference between the calculated acceleration and the experimental acceleration, when the pulley’s moment of inertia is included in the acceleration calculation. All data points fall within the limits of agreement when analyzed using the Bland–Altman plot. The LiTA acceleration measurement instrument can serve as an alternative apparatus for experiments on linear motion dynamics. It provides a feasible solution for measuring acceleration in situations where conventional experimental equipment is limited or unavailable.